How Does Work-Life Balance Influence Expatriates’ Working Performance? : The Case of Malaysia - Ahmad Zahar, Nur Yuha Zulaikha (2011)
This research examines the important factors that play significant parts in the life of expatriates as they attempt to gain work-life balance. If reaching work-life balance is important for an employee, it is even far more important for expatriates as they face a lot of challenges living thousands of miles away from their family members and friends whom they always seek support from. Understanding the true meaning of work-life balance is essential as it mirrors how the expatriate’s performance is measured at work. Even though previous researches had examined the issue of work-life balance, however the focus on expatriate’s work performance is still very few. There is still a lot to learn about the life of an expatriate and the real challenges they encounter living overseas. Although they are seen as a group of people that benefits a lot from a company, however there are costs they have to pay for these that reflect their way of life and work. It highlights the actual reasons behind expatriate stress and how self-efficacy is not a major instrument in their everyday experiences towards attaining work-life balance. This paper uses semi-structured interviews with expatriates found in Kuala Lumpur, Malaysia and how they deal with work-life balance. A literature review is covered before analysing the real experiences faced by the respondents of both gender regardless of their age and occupation. Only then the findings are peeled one by one in having a better grasp of how an expatriate’s performance is relied on their way of reaching work-life balance. At the end, a proper recommendation is highlighted to show that the expatriates can still depend on their company to seek help from as well as their family members as their main pillar of strength to survive living the ever challenging life offshore.Companies still need to provide necessary support services to the expatriates to assist them in any issues faced in the host country and help them live a comfortable life throughout their expatriation.